Implementing workplace health promotion – role of middle managers. Issue 2 (3rd April 2017) - Justesen, Just Bendix; Eskerod, Pernille; Christensen, Jeanette Reffstrup; Sjøgaard, Gisela
Abstract : Purpose: The purpose of this paper is to address a missing link between top management and employees when it comes to understanding how to successfully implement and embed workplace health promotion (WHP) as a strategy within organizations: the role of the middle managers. Design/methodology/approach: A conceptual framework based on review of theory is applied within an empirical multi-case study that is part of a health intervention research project on increased physical activity among office workers. The study involves six Danish organizations. Findings: Middle managers play a key role in successful implementation of WHP, but feel uncertain about their role, especially when it comes to engaging with their employees. Uncertainty about their role appears to make middle managers reluctant to take action on WHP and leave further action to top management instead. Research limitations/implications: Limitations included the middle managers' low attendance at the half-day seminar on strategic health (50 percent attendance), the fact that they were all office workers and they were all from Denmark. Practical implications: Middle managers ask for more knowledge and skills if they are to work with WHP in daily business. Social implications: Implementing and embedding WHP as a health strategy raises ethical issues of interfering with employees' health, is seen as the employee's personal responsibility. Originality/value: This study adds to knowledge of the difficulties of implementing and embedding WHP activities in the workplace and suggests an explicit and detailed research design.